Early Loaded Single Implant Reinforced Mandibular Overdenture - K. Nischal; R. Chowdhary (Hindawi Limited, 2016)
Rehabilitating atrophied mandible with two-implant supported denture is a common treatment modality for implant retained removable overdenture in mandible. This paper aims to design a treatment modality where single implant reinforced overdenture is fabricated for a severely atrophied mandibular ridge with early loading protocol. Results of studies have shown that a single implant mandibular overdenture significantly increases the satisfaction and quality of life of patients with edentulism. Midline fracture of the prosthesis is the most common complication related to single implant and two-implant retained mandibular overdentures. To manage such complication, a thin metal mesh is used to reinforce the overdenture and also to make the prostheses lighter and cost effective as compared to conventional cast metal framework.